2014
DOI: 10.4103/0970-4388.140950
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric evaluation of adenoids, upper airway, maxilla, velum length, need ratio for determining velopharyngeal incompetency in subjects with unilateral cleft lip and palate

Abstract: Decreased Adenoids, restricted airway, small, retruded maxilla, smaller velum length and larger need ratio larger were seen in the cleft group as compared to the non-cleft group, which was suggestive of VPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Trindade et al (2015) evaluated the nasal airways of children with UCLP using acoustic rhinometry and showed that the UCLP children had narrower nasal cross-sectional areas than the noncleft children. Imamura et al (2002) and Gohilot et al (2014) reported that, when compared to a control group of noncleft skeletal class I participants, UCLP children and adolescents had a more retruded positioned maxilla and had narrowed nasal airway volume. Aras et al (2012) and Ö lmez-Gürlen et al (2015) evaluated the differences in nasal passage volume between UCLP patients and noncleft individuals using similar boundaries than our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trindade et al (2015) evaluated the nasal airways of children with UCLP using acoustic rhinometry and showed that the UCLP children had narrower nasal cross-sectional areas than the noncleft children. Imamura et al (2002) and Gohilot et al (2014) reported that, when compared to a control group of noncleft skeletal class I participants, UCLP children and adolescents had a more retruded positioned maxilla and had narrowed nasal airway volume. Aras et al (2012) and Ö lmez-Gürlen et al (2015) evaluated the differences in nasal passage volume between UCLP patients and noncleft individuals using similar boundaries than our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous comparative CLP studies have enrolled non-CLP participants with normal occlusion participants as the control group, and comparisons may have been made between class III patients with CLP and class I normal controls (Aras et al, 2012; Celikoglu et al, 2014; Gohilot et al, 2014; Pimenta et al, 2015). To our knowledge, no previous studies evaluating the nasal volume of UCLP patients correlated with skeletal class III participants have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Gohilot et al 8 mentioned that a reduction in the nasopharynx area was accompanied by a decrease in lateral and vertical maxillary growth after palatoplasty surgery, which can be determined by nasopharynx examination through lateral cephalometric radiograph analysis in postpalatoplasty. 8 Reduction of nasopharynx area was one of the factors in the occurrence of a posterior crossbite that cannot be seen clinically, but can be measured by performing radiographic assessments using radiographic analysis lateral cephalometry as a routine diagnostic tool in determining orthodontic cases and for assessing nasopharynx area. 9 Huddart and Bodenham explained that the measurement of a posterior crossbite in the primary teeth of CLP children after palatoplasty can be done quite easy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the airways of patients affected by CLP, and some studies utilized 2-dimensional radiographs. Gohilot et al (2014) and Trotman and Ross (1993) used lateral cephalometric radiographs and found that patients with CLP have a narrow upper airway, maxillary deficiency, and a short soft palate. With the development of 3-dimensional (3D) technology, cone-beam computed tomography (CBCT) has gradually become a widely accepted diagnostic technique for evaluating the upper airway due to its advantages, which include a lower radiation dose, shorter image acquisition time, and lower cost (Aras et al, 2012).…”
Section: Introductionmentioning
confidence: 99%